The translational sciences clinic: From bench to bedside - Halushka, Perry (J Clin Transl Sci, 2020)
The mission of the National Center for Advancing Translational Science (NCATS) is to speed the development of drugs from discovery to approval to dissemination and implementation. The Medical University of South Carolina and the South Carolina Clinical and Translational Research Institute host a NCATS funded predoctoral T32 training grant (TL1) with a focus on translational research. Doctoral (PhD) trainees working at the bench usually have limited opportunity for clinical interactions to gain a clinical perspective on the diseases that are the focus of their dissertation research. To provide TL1 trainees with an opportunity to see how their research could be translated into improved patient care, we developed a mentored clinical exposure experience named the Translational Sciences Clinic. Trainees spend one-half day a week in a clinic related to their basic science research for one semester interacting with patients and clinical mentors and discuss the most recent literature related to the patient’s clinical problem with their clinical mentor. Trainees deemed the rotation to be one of the most rewarding experiences that they had as a part of their predoctoral training. Participating clinical mentors were also very enthusiastic and agreed that they would be willing to mentor similar trainees again.